Penggunaan Kontrasepsi pada Perempuan dengan HIV di Dunia - Dayu Marista; Ira Nurmala (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: HIV infection is a public health problem. In 2019, more than 38 million people were living with HIV, and more than 1.7 million people contracted HIV. On the other hand, it was reported that infant morbidity and mortality remained high, with more than 160,000 infants contracting HIV and more than 100,000 dying from AIDS-related causes. Increased access and improved service programs to control HIV transmission from mother to child are in line with the increasing number of pregnant women with HIV. Women with HIV and their partners need to plan carefully before deciding to have children. Women living with HIV and their partners need to take advantage of services that provide information and contraceptive tools to prevent unplanned pregnancies. The study aimed to understand how HIV-infected women chose contraceptives.Method: Search for articles with a systematic review using four databases consisting of Pubmed, Science Direct, Sage, and Emerald Insight with a publication range of 2017-2020. The keywords used were contraceptive use AND HIV women. The inclusion criteria used were women with HIV aged 15-49 years and used a cross-sectional design.Results: The findings indicated that injections, condoms, and implants were the most common methods of contraception used by women with HIV. Motivation for contraceptive use in women with HIV is influenced by age, marital status, knowledge, number of children, education, previous history of contraceptive use, history of childbirth, lack of fertility desires, income, residence, CD4 count, child's HIV status and partner's HIV status.